Low-emission liquid hydrogen valve material with amorphous / crystalline interface and preparation method thereof
By forming a combination technology of SiC-MWCNT-Ni cermet composite layer, eutectic ceramic feed powder and high-entropy alloy coating on the substrate surface of the liquid hydrogen valve, the leakage problem of liquid hydrogen valve under extreme operating conditions is solved, and the leakage problem of liquid hydrogen valve is achieved. It has high sealing and low leakage rate, and is suitable for working conditions from -269°C to 70MPa.
Patent Information
- Application Number
- CN202410745572.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-06-11
AI Technical Summary
Liquid hydrogen valves are prone to leakage under extreme operating conditions. The difference in thermal expansion coefficient and elastic modulus between existing coatings and fillers or substrates leads to micro gaps and microcracks, hydrogen atoms penetrate through the sealing structure, and electrochromium plating is environmentally friendly. Poor ceramic bonding strength with the substrate is low, resulting in insufficient sealing performance.
Prepare SiC-MWCNT-Ni cermet composite layer on the surface of carbon steel, alloy steel or stainless steel matrix to form eutectic ceramic feed powder, prepare an amorphous ceramic layer by plasma spraying, and form it on the surface of the amorphous layer through thermal spraying technology The high-entropy alloy coating forms a crystal cermet layer/amorphous ceramic layer/high-entropy alloy layer, a gradient transition thermal expansion coefficient and elastic modulus, forming an irreversible hydrogen trap to prevent hydrogen penetration.
It achieves low leakage rate and high sealing at the minimum service temperature of -269℃ and maximum working pressure of 70MPa. The leakage rate at the stem seal is ≦3.14*10-8mg·s-1·mm-1, and leakage at the valve body seal is ≦ The amount is ≦50ppmv, which improves the sealing performance and reliability of liquid hydrogen valves.
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid hydrogen valve material and a preparation method thereof, and in particular to a low-emission liquid hydrogen valve material with an amorphous / crystalline interface and a preparation method thereof, and belongs to the fields of new energy, advanced manufacturing, new materials and surface engineering. Background Art
[0002] The hydrogen energy industry is an important development direction in the future, and valves are an indispensable part of the hydrogen energy industry. Globally, hydrogen storage and transportation include normal temperature and high pressure, low temperature and high pressure, or low temperature liquid. Liquid hydrogen has a high density and has good development prospects in hydrogen storage and transportation. However, in extreme working conditions of liquid hydrogen, the sealing parts such as the matching of the packing of the liquid hydrogen valve with the valve stem and the stuffing box, and the connection between the valve body and the valve cover are very prone to leakage, which is an important problem facing liquid hydrogen valves.
[0003] Applying coating on the surface of sealing parts (such as valve stem, valve body and valve cover, etc.) to improve its surface wear and corrosion resistance is an effective method to reduce leakage rate and improve sealing. CN201210462579.4 discloses a chrome plating process for valve stems, which adds a certain amount of rare earth elements and fluoride ions to the plating solution, uses rare earth elements to reduce the concentration of chromic anhydride, widens the plating temperature range (10-50°C) and the cathode current density range (5-30 A / dm 2 ), reduce the groove pressure, improve the brightness and hardness of the coating, and make the chrome plating production achieve low temperature, low energy consumption, low pollution and high efficiency. CN201410056119.0 discloses a hydrogenation valve and its processing method. First, according to the characteristics of the hydrogenation valve pressure plate and the valve stem connecting nut, a suitable self-lubricating polymer material is prepared or selected, and the self-lubricating polymer material is sprayed on the valve stem surface by using the polymer material spraying surface treatment technology. The sprayed polymer material solidifies for more than 30 minutes at room temperature, and then the valve stem with the self-lubricating material sprayed on the surface is rubbed with the hydrogenation valve joint nut to achieve automatic centering and avoid leakage caused by valve stem wear. CN201711125147.3 sprays a ceramic coating on the valve stem to improve its impact resistance, wear resistance, corrosion resistance and hardness, which can improve the sealing performance of the valve.
[0004] Existing metal, ceramic, and polymer-based coatings mainly reduce leakage by reducing friction and wear. However, in the existing technology, there is a large difference in thermal expansion coefficient and elastic modulus between the coating and the filler, and between the coating and the substrate. Micro gaps are easily formed due to interface mismatch in low-temperature liquid and normal temperature and high pressure, low temperature and high pressure working conditions, and micro cracks and leakage occur between the coating and the substrate due to residual stress; due to the small diameter of hydrogen atoms, they may also penetrate through the sealing structure and cause leakage in low-temperature liquid and normal temperature and high pressure, low temperature and high pressure working conditions; in addition, electroplating chromium is not environmentally friendly, and the bonding strength between ceramic and polymer-based coatings and the substrate is low, so coating cracks are prone to occur under the above working conditions. In order to further improve the sealing performance of liquid hydrogen valves, it is urgent to develop new low-emission liquid hydrogen valve materials and preparation technologies. Summary of the invention
[0005] In view of the problem that the current liquid hydrogen valve is prone to leakage and the sealing performance needs to be improved urgently, the present invention proposes to first prepare a SiC-MWCNT-Ni metal ceramic composite layer with high density C- and Si-dangling bonds on the surface of carbon steel, alloy steel or stainless steel base material, then prepare eutectic ceramic feed powder and use plasma spraying to prepare an amorphous intermediate layer, and finally use thermal spraying technology to prepare a high entropy alloy coating on the surface of the amorphous layer and pre-oxidize to form a dense oxide film. Through the structure of crystal metal ceramic layer / amorphous ceramic layer / crystal high entropy alloy layer, a gradient transition of thermal expansion coefficient from low to high and elastic modulus from high to low is formed, thereby avoiding the control of sealing position change and the relief of interface residual stress; the crystal high entropy alloy layer has high plastic toughness and can coordinate deformation to improve sealing, and uses high density dangling bonds, two layers of amorphous / crystal interface and dense oxide film on the surface to prevent hydrogen penetration and reduce leakage, thereby preparing a low-emission liquid hydrogen valve material with an amorphous / crystal interface.
[0006] The low-emission liquid hydrogen valve material with an amorphous / crystal interface of the present invention is characterized in that its substrate is carbon steel, alloy steel or stainless steel, and the surface of the substrate is sequentially provided with a SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds, an Al2O3-ZrO2-YAG amorphous ceramic coating, and a high-entropy alloy coating; wherein the SiC-MWCNT-Ni metal ceramic composite layer has a thickness of 30-45 μm and contains 4×10 17 ~6×10 18 / cm 3High density of C- and Si-dangling bonds; the thickness of the Al2O3-ZrO2-YAG amorphous ceramic coating is 100~200μm, the porosity is 1.0~1.5%, the crystalline / amorphous interface formed by the amorphous ceramic coating and the SiC-MWCNT-Ni metal ceramic composite layer is an irreversible hydrogen trap, and its activation energy is >70kJ / mol; the high entropy alloy coating is AlCoCrFeNiCu, with a molar ratio of Al:Co:Cr:Fe:Ni:Cu=(1~1.2):1:(1~1.2):1:1:1, and there are high-density vacancy defects and lattice distortion defects in the coating. The initial high entropy alloy coating area is 300~350μm thick, the coating porosity is 0.5~1.0%, the roughness Ra5.0~6.5μm, the grain size of the coating organization is 1.5~2.5μm, the coating phase is FCC+BCC dual-phase structure, the high entropy alloy coating and the amorphous ceramic coating The crystalline / amorphous interface formed by the layer is an irreversible hydrogen trap, and its activation energy is greater than 65kJ / mol; the surface of the AlCoCrFeNiCu high entropy alloy coating has a plastic layer formed by rolling, the thickness of the initial plastic layer zone is 10-30μm, the grain size of the plastic layer organization is 30-50nm, the porosity is 0.01-0.1%, and the phase of the plastic layer remains a FCC+BCC dual-phase structure; the surface of the plastic layer has a dense Al2O3 ceramic oxide film of 1-2.5μm thick generated in situ, and the surface roughness after grinding is Ra0.08-0.1; the low-emission liquid hydrogen valve material with an amorphous / crystal interface of the present invention has a minimum service temperature of -269°C, a maximum working pressure of 70MPa, and a permeability reduction factor PRF of 300-500; the leakage rate of the valve stem seal of the liquid hydrogen valve manufactured using the low-emission liquid hydrogen valve material with an amorphous / crystal interface is ≦3.14*10 -8 mg·s -1 mm -1 , the leakage at the valve body seal is ≤50ppmv.
[0007] The method for preparing the low-emission liquid hydrogen valve material with an amorphous / crystal interface of the present invention is characterized by comprising the following steps in sequence:
[0008] (1) Preparation of SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds: Using carbon steel, alloy steel or stainless steel as the substrate, first use white corundum micropowder with a particle size of 240-320 mesh to micro-sandblast the substrate surface to roughen the surface. The sandblasting pressure is 0.1 MPa, the sandblasting angle is 65-85°, and the sandblasting distance is 50-70 mm. After sandblasting for 5-10 minutes, ultrasonic cleaning is carried out in anhydrous ethanol for 15-30 minutes and cold air drying is used. Then, the average particle size is 50-60 nm and the specific surface area is 80-90 m 2 / g of nano-SiC powder, with a diameter of 10~20nm, a length of 5μm~15μm, and a specific surface area of 200~230m 2 / g of multi-walled carbon nanotubes MWCNT are mixed with NiSO4, NiCl2, and H3BO3 to prepare a mixed solution, wherein the concentration of NiSO4 is 230-280g / L, the concentration of NiCl2 is 30-40g / L, the concentration of H3BO3 is 30-40g / L, the content of nano-SiC is 2.5-3g / L, and the content of multi-walled carbon nanotubes MWCNT is 0.4-0.6g / L. After the mixed solution is ultrasonically treated for 30-40min, Tween 80 is added dropwise according to 1-2% of the volume of the mixed solution, and HCl is added dropwise to adjust the pH value of the mixed solution to 3-4.5. A composite electrodeposition solution with a Zeta potential of 20-25mv is obtained while adding dropwise and magnetic stirring. The substrate is placed in the composite electrodeposition solution as a cathode, and a pure Ni plate is used as an anode. The current density is controlled to be 2.5-4.5A / dm 2 , pulse frequency 1000Hz, pulse duty cycle 30~50%, electrodeposition temperature 50~60℃, deposition time 40~60min, a layer with a thickness of 30~45μm and containing 4×10 17 ~6×10 18 / cm 3 SiC-MWCNT-Ni metal ceramic composite layer with high density of C- and Si-dangling bonds;
[0009] (2) Preparation of eutectic ceramic feed powder: First, C 16 H 33 (CH3)3NBr, isopropanol, and n-hexane were added to deionized water, and the weight percentage was C 16 H 33(CH3)3NBr accounts for 15% to 32%, isopropanol accounts for 7% to 15%, n-hexane accounts for 6% to 15%, and the rest is ionized water. Stir with a magnetic stirrer at 60 to 90 ° C for 3 to 10 hours, and then place it for 6 to 12 hours to form a reverse microemulsion; weigh Al(NO3)3, ZrOCl2, and Y(NO3)3, the molar ratio of the three reagents is 0.63: (0.37-x): x, and x / (0.37-x)=0.04~0.12, add the three reagents to the prepared reverse microemulsion, control the total molar concentration of the three reagents to 0.6~0.8 mol / L, then add ammonia water to adjust the pH value of the solution to 8~9, and stir with a magnetic stirrer at 60 to 90 ° C for 3 to 12 hours. Then, the mixture was placed for 10 to 24 hours to form an Al(OH)3-Zr(OH)4-Y(OH)3 eutectic precursor sol, 1 to 2 wt.% PVA was added, and then spherical powder agglomerates were prepared by spray drying. The spherical powder agglomerates were placed in a vacuum sintering furnace and sintered at 1400 to 1500 °C for 60 to 90 minutes to obtain a eutectic ceramic feed powder with a particle size of 30 to 40 μm and a phase composition of α-Al2O3, c-ZrO2 and YAG phase, i.e., Y3Al5O 12 ;
[0010] (3) Preparation of amorphous ceramic coating: First, the substrate on which the SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds was formed was placed in liquid nitrogen for 1 to 2 hours to cool it to below -180°C; the substrate surface that had been cooled to below -180°C was plasma sprayed with eutectic ceramic feed powder. The current during spraying was 600 to 650A, the power was 35 to 45kW, the argon flow rate was 45L / min, the hydrogen flow rate was 7L / min, the powder feeding rate was 30 to 35g / min, and the spraying distance was 100 to 120mm; an Al2O3-ZrO2-YAG amorphous ceramic coating with a thickness of 100 to 200μm and a porosity of 1.0 to 1.5% was formed under high supercooling. The crystalline / amorphous interface formed between the amorphous ceramic coating and the SiC-MWCNT-Ni metal ceramic composite layer was an irreversible hydrogen trap with an activation energy of >70kJ / mol;
[0011] (4) Preparation of surface high entropy alloy coating: Al, Co, Cr, Fe, Ni, and Cu powders were weighed in a molar ratio of (1-1.2):1:(1-1.2):1:1:1, and the weighed raw material powders were subjected to planetary ball milling at a ball milling speed of 300-400 r / min and a ball-to-material ratio of 10:1. Al2O3 ceramic grinding balls with a diameter of 5 mm were used for ball milling for 24-48 h. After ball milling, AlCoCrFeNiCu high entropy alloy powder with an average particle size of 30-40 μm was prepared by filtration, spray drying, agglomeration sintering, crushing, and air flow classification. The AlCoCrFeNiCu high entropy alloy powder was used to form an amorphous ceramic coating on the substrate surface by supersonic flame spraying. The hydrogen flow rate during spraying was 560-580 m 3 / s, oxygen flow rate 180~200m 3 / s, nitrogen flow rate 18~20m 3 / s, spray distance 200~250mm, powder feeding rate 40~45g / min; the high entropy alloy coating with high-density vacancy defects and lattice distortion defects after spraying, the initial high entropy alloy coating area thickness is 300~350μm, the coating porosity is 0.5~1.0%, the roughness Ra5.0~6.5μm, the coating grain size is 1.5~2.5μm, the coating phase is FCC+BCC dual-phase structure, the crystalline / amorphous interface formed by the high entropy alloy coating and the amorphous ceramic coating is an irreversible hydrogen trap, and its activation energy is>65kJ / mol;
[0012] (5) Formation of plastic deformation layer on the surface of high entropy alloy coating: The surface of high entropy alloy coating was rolled using a diamond indenter with a tip arc radius of 1.0 mm. The linear speed of the rolling process was 50-200 m / min, the feed rate was 0.05-0.15 mm / r, the pre-pressing amount was 0.01-0.03 mm, the load was 100-200 N, and the angle between the indenter axis and the surface normal of the high entropy alloy coating was 30-60°. During the rolling process, the diamond indenter caused severe plastic deformation on the coating surface, and the high points of the surface contour flowed into the low points. After rolling, the surface roughness of the high entropy alloy coating was Ra0.06-0.08, and a plastic deformation layer was formed on the surface of the coating. The thickness of the initial plastic deformation layer was 10-30 μm, the grain size of the plastic deformation layer was 30-50 nm, and the porosity was 0.01-0.1%. The phase of the plastic deformation layer remained a FCC+BCC dual-phase structure.
[0013] (6) Oxidation treatment of the surface plastic deformation layer: The substrate on which the surface plastic deformation layer of the high entropy alloy coating is formed is placed in a vacuum furnace for oxidation treatment in a mixed atmosphere of argon and oxygen, with a heating rate of V = 5~15℃ / min, the oxidation temperature is controlled at 900+12lnV℃, and the oxidation time is 1~2h. After the treatment, Ar gas with a flow rate of 50~60L / h is introduced for rapid cooling. A dense Al2O3 ceramic oxide film with a thickness of 1~2.5μm is generated in situ on the surface of the plastic deformation layer. The dangling bond density in the SiC-MWCNT-Ni metal ceramic composite layer remains unchanged, the amorphous ceramic coating remains amorphous and no crystalline phase is precipitated, and the physical phase of the high entropy alloy coating remains unchanged;
[0014] (7) Preparation of low-emission liquid hydrogen valve material with amorphous / crystalline interface: First, the substrate surface after surface plastic deformation layer oxidation treatment is ground with W0.5 and W0.25 grinding pastes in turn, and the surface roughness reaches Ra0.08~0.1, then ultrasonically cleaned in anhydrous ethanol for 10~15min and blown dry with cold air, and then the blown-dried valve stem, valve stem and valve cover substrate are assembled with matching packing, spring and bearing parts, and the preparation of low-emission liquid hydrogen valve material with amorphous / crystalline interface is completed. Its minimum service temperature is -269℃, the maximum working pressure is 70MPa, and its permeability reduction factor PRF is 300~500; the leakage rate of the valve stem seal of the liquid hydrogen valve made of low-emission liquid hydrogen valve material with amorphous / crystalline interface is ≦3.14*10 -8 mg·s -1 mm -1 , the leakage at the valve body seal is ≤50ppmv.
[0015] The method for preparing a low-emission liquid hydrogen valve material having an amorphous / crystalline interface of the present invention is further characterized in that:
[0016] (1) When preparing a SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds, the base material is first processed into a valve stem, valve body or valve cover of a liquid hydrogen valve; the ultrasonic frequency and power during ultrasonic cleaning and ultrasonic treatment are 40 kHz and 100 W, respectively;
[0017] (2) When preparing eutectic ceramic feed powder, the initial vacuum degree of sintering is 1~5Pa, the heating rate is 5~10℃ / min, the temperature is kept at 500~550℃ for 1h during sintering, and the furnace is cooled after sintering;
[0018] (3) When preparing amorphous ceramic coatings, compressed air at 0.6-0.8 MPa is used to cool the substrate during thermal spraying;
[0019] (4) When preparing AlCoCrFeNiCu high entropy alloy powder, anhydrous ethanol and PEG2000 were added to the ball mill, and the mass ratio of the added amount to the raw material powder was 25-30% and 1-2%, respectively. During the ball milling process, 0.05-0.10 MPa argon gas was filled for protection, and a 400-mesh screen was used for filtration after the ball milling. During the spray drying, the atomizing disk speed was 6000-7000 r / min, and the drying temperature was 110-120 °C. During the sintering process of the powder agglomerate after spray drying, the initial vacuum degree was 1-5 Pa, the heating rate was 5-10 °C / min, and the temperature was kept at 500-550 °C for 1 h during the sintering process. After the sintering was completed, the powder was cooled with the furnace.
[0020] (5) Before the surface of the high-entropy alloy coating is subjected to micro-sandblasting treatment with 2-5 μm Al2O3 micropowder, the sandblasting pressure is 0.08 MPa, the sandblasting angle is 45-55°, and the sandblasting distance is 50-70 mm. After sandblasting for 1-3 min, ultrasonic cleaning is performed in anhydrous ethanol for 15-30 min. The ultrasonic frequency and power during ultrasonic cleaning are 40 kHz and 100 W, respectively. Cold air drying is used after ultrasonic cleaning.
[0021] (6) During oxidation treatment of the surface plastic deformation layer, the oxygen content in the mixed atmosphere of argon and oxygen is 1~5vol%. During oxidation treatment, the vacuum in the furnace is first pumped to 2*10 -2 Below Pa;
[0022] (7) When preparing low-emission liquid hydrogen valve materials with amorphous / crystalline interfaces, the ultrasonic frequency and power during ultrasonic cleaning are 40 kHz and 100 W, respectively.
[0023] The advantages of the present invention are as follows: (1) The low-emission liquid hydrogen valve material with an amorphous / crystal interface of the present invention is a metal-ceramic composite layer / amorphous ceramic layer / high entropy alloy layer formed on the surface of a metal material substrate in sequence. The metal-ceramic composite layer / amorphous ceramic layer / high entropy alloy layer contains MWCNT, Al2O3 and metal respectively, and its thermal expansion coefficient increases in sequence, while the elastic modulus decreases in sequence from the presence of SiC, Al2O3 to metal. The material composition and structural design of the present invention can reduce the difference in thermal expansion coefficient and elastic modulus between layers, thereby reducing the residual stress of the coating, avoiding the problem of huge difference in thermal expansion coefficient when directly forming metal, ceramic, and polymer material coatings on the surface of a metal substrate in the prior art, avoiding microcracks and leakage, and improving the sealing and reliability of the valve. (2) While ensuring performance, the metal-ceramic composite layer / amorphous ceramic layer / high entropy alloy layer has a reduced thermal expansion coefficient due to the introduction of MWCNT and ceramic phase, which can avoid the valve parts prepared from excessive dimensional changes and leakage during service under normal temperature and high pressure, low temperature and high pressure or low temperature liquid conditions. (3) The dense oxide film formed in situ after the oxidation treatment of the surface plastic deformation layer of the low-emission liquid hydrogen valve material with an amorphous / crystal interface of the present invention has good bonding with the plastic deformation layer, is not easy to fall off during the opening and closing process of the valve, and has good wear resistance, which can improve the sealing of the valve. (4) The high-entropy alloy plastic deformation layer on the surface of the low-emission liquid hydrogen valve material with an amorphous / crystal interface of the present invention realizes the strengthening of the high-entropy alloy, improves the deformation resistance of the valve stem, valve body, valve cover and other sealing parts, and is conducive to obtaining excellent sealing. (5) The SiC-MWCNT-Ni metal ceramic composite layer, Al2O3-ZrO2-YAG amorphous ceramic layer, and the dense Al2O3 oxide film on the surface of the low-emission liquid hydrogen valve material with an amorphous / crystal interface of the present invention all have excellent hydrogen penetration resistance, which can improve the sealing and reliability of the valve. The SiC-MWCNT-Ni metal ceramic composite layer contains high-density C- and Si-dangling bonds, which can capture hydrogen and prevent hydrogen from diffusing into the matrix to cause leakage or even hydrogen embrittlement. The Al2O3-ZrO2-YAG amorphous ceramic layer matches the adjacent metal ceramic layer and high-entropy alloy layer to form two amorphous / crystalline interfaces, both of which become irreversible hydrogen traps with an activation energy higher than 60kJ / mol, with a strong ability to capture hydrogen, prevent hydrogen from diffusing into the matrix, and reduce the risk of leakage. The AlCoCrFeNiCu high-entropy alloy layer has a dense oxide film on the surface and a dense plastic deformation layer on the subsurface. The entire high-entropy alloy layer has high-density vacancies and distortions, which can prevent hydrogen from diffusing into the matrix and reduce the risk of leakage. (6) The minimum service temperature of the low-emission liquid hydrogen valve material with amorphous / crystalline interface of the present invention is -269°C, and the maximum working pressure is 70MPa; the leakage rate of the valve stem seal of the liquid hydrogen valve manufactured using the low-emission liquid hydrogen valve material with amorphous / crystalline interface of the present invention is ≤3.14*10-8 mg·s -1 mm -1 The leakage of the valve body seal is ≤50ppmv, and its sealing grade is AH according to ISO 15848-1 and GB / T 40079 standards. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the structure of the low-emission liquid hydrogen valve material with amorphous / crystalline interface of the present invention.
[0025] Figure 2 Schematic diagram of the method for preparing the low-emission liquid hydrogen valve material with amorphous / crystalline interface of the present invention. DETAILED DESCRIPTION
[0026] Example 1:
[0027] A low-emission liquid hydrogen valve material with an amorphous / crystal interface, the structure of which is as follows Figure 1 As shown in the figure, the substrate is carbon steel, alloy steel or stainless steel, and the surface of the substrate is composed of a SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds, an Al2O3-ZrO2-YAG amorphous ceramic coating, and a high-entropy alloy coating. The SiC-MWCNT-Ni metal ceramic composite layer is 32 μm thick and contains 5×10 17 / cm 3High density of C- and Si-dangling bonds; the thickness of the Al2O3-ZrO2-YAG amorphous ceramic coating is 114μm, the porosity is 1.05%, the crystalline / amorphous interface formed by the amorphous ceramic coating and the SiC-MWCNT-Ni metal ceramic composite layer is an irreversible hydrogen trap with an activation energy of 76kJ / mol; the high entropy alloy coating is AlCoCrFeNiCu, with a molar ratio of Al:Co:Cr:Fe:Ni:Cu= 1:1:1:1:1:1, the coating has high-density vacancy defects and lattice distortion defects, the initial high-entropy alloy coating area thickness is 320μm, the coating porosity is 0.6%, the roughness Ra is 5.0μm, the coating grain size is 1.5μm, the coating phase is FCC+BCC dual-phase structure, the crystalline / amorphous interface formed by the high-entropy alloy coating and the amorphous ceramic coating is an irreversible hydrogen trap with an activation energy of 67kJ / mol, the surface of the AlCoCrFeNiCu high-entropy alloy coating has a plastic layer formed by rolling, the initial plastic layer thickness is 15μm, and the plastic layer composition is 10μm. The grain size of the fabric is 43nm, the porosity is 0.03%, and the phase of the plastic layer is maintained as a FCC+BCC dual-phase structure; the surface of the plastic layer has an in-situ generated 1.3μm thick dense Al2O3 ceramic oxide film, and the surface roughness after grinding is Ra0.08; the minimum service temperature of the low-emission liquid hydrogen valve material with an amorphous / crystalline interface of the present invention is -269℃, the maximum working pressure is 70MPa, and the permeability reduction factor PRF is 320; the leakage rate of the valve stem seal of the liquid hydrogen valve manufactured using the low-emission liquid hydrogen valve material with an amorphous / crystalline interface is ≦2.25*10 -8 mg·s -1 mm -1 , the leakage at the valve body seal is 46ppmv.
[0028] The preparation method of the material is as follows Figure 2 As shown, the following steps are included:
[0029] (1) Preparation of SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds: Carbon steel, alloy steel or stainless steel is used as the substrate and processed into the valve stem, valve body or valve cover of the liquid hydrogen valve. The substrate surface is firstly subjected to micro-sandblasting treatment with white corundum micropowder with a particle size of 240 mesh to roughen the surface. The sandblasting pressure is 0.1 MPa, the sandblasting angle is 65°, and the sandblasting distance is 50 mm. After sandblasting for 5 minutes, ultrasonic cleaning is performed in anhydrous ethanol for 15 minutes. The ultrasonic frequency and power during ultrasonic cleaning are 40 kHz and 100 W, respectively, and cold air drying is used. Then, the substrate with an average particle size of 51 nm and a specific surface area of 82 m 2 / g of nano-SiC powder, with a diameter of 11nm, a length of 6μm, and a specific surface area of 210m 2 / g of multi-walled carbon nanotubes MWCNT are mixed with NiSO4, NiCl2, and H3BO3 to prepare a mixed solution, wherein the NiSO4 concentration is 230g / L, the NiCl2 concentration is 30g / L, the H3BO3 concentration is 30g / L, the nano-SiC content is 2.5g / L, and the multi-walled carbon nanotube MWCNT content is 0.4g / L. The mixed solution is ultrasonically treated for 30min, and the ultrasonic frequency and power during the ultrasonic treatment are 40 kHz and 100 W, respectively. Then, Tween 80 is added dropwise at 1% of the volume of the mixed solution, and HCl is added dropwise to adjust the pH value of the mixed solution to 3. A composite electrodeposition solution with a Zeta potential of 21mv is obtained while the mixture is added dropwise and magnetically stirred. The substrate is placed in the composite electrodeposition solution as a cathode, and a pure Ni plate is used as an anode. The current density is controlled to be 2.6A / dm 2 , pulse frequency 1000Hz, pulse duty cycle 30%, electrodeposition temperature 50℃, deposition time 40min, a 32μm thick layer containing 5×10 17 / cm 3 SiC-MWCNT-Ni metal ceramic composite layer with high density of C- and Si-dangling bonds;
[0030] (2) Preparation of eutectic ceramic feed powder: First, C 16 H 33 (CH3)3NBr, isopropanol, and n-hexane were added to deionized water, and the weight percentage was C 16 H 33 (CH3)3NBr accounts for 16%, isopropanol accounts for 7%, n-hexane accounts for 7%, and the rest is ionized water. Stir with a magnetic stirrer at 60℃ for 3h, and then leave it for 7h to form a reverse microemulsion. Weigh Al(NO3)3, ZrOCl2, and Y(NO3)3. The molar ratio of the three reagents is 0.63:0.32:0.05. Add the three reagents to the prepared reverse microemulsion to control the total molar concentration of the three reagents to 0.6 mol / L. Then add ammonia water to adjust the pH value of the solution to 8. Stir with a magnetic stirrer at 60℃ for 4h. Then, the mixture was placed for 10 hours to form an Al(OH)3-Zr(OH)4-Y(OH)3 eutectic precursor sol, 1 wt.% PVA was added, and then spherical powder agglomerates were prepared by spray drying. The spherical powder agglomerates were placed in a vacuum sintering furnace, the initial vacuum degree of sintering was 2 Pa, the heating rate was 6 ° C / min, the temperature was kept at 500 ° C for 1 hour during the sintering process, and the temperature was sintered at 1400 ° C for 60 minutes. After the sintering was completed, the furnace was cooled to obtain a eutectic ceramic feed powder with a particle size of 32 μm and a phase composition of α-Al2O3, c-ZrO2 and YAG phase, i.e., Y3Al5O 12 ;
[0031] (3) Preparation of amorphous ceramic coating: First, the substrate on which the SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds was formed was placed in liquid nitrogen for 1 hour to cool it to -181°C; the surface of the substrate that had been cooled to -181°C was plasma sprayed with eutectic ceramic feed powder. The current during spraying was 600A, the power was 35kW, the argon flow rate was 45L / min, the hydrogen flow rate was 7L / min, the powder feeding rate was 30g / min, and the spraying distance was 100mm; during the thermal spraying process, the substrate was cooled with 0.6MPa compressed air to form an Al2O3-ZrO2-YAG amorphous ceramic coating with a thickness of 114μm and a porosity of 1% under high supercooling. The crystalline / amorphous interface formed by the amorphous ceramic coating and the SiC-MWCNT-Ni metal ceramic composite layer is an irreversible hydrogen trap with an activation energy of 76kJ / mol;
[0032] (4) Preparation of surface high entropy alloy coating: Al, Co, Cr, Fe, Ni, and Cu powders were weighed in a molar ratio of 1:1:1:1:1:1, and the weighed raw powders were subjected to planetary ball milling at a ball milling speed of 310 r / min and a ball-to-material ratio of 10:1. Al2O3 ceramic grinding balls with a diameter of 5 mm were used for ball milling for 24 h. Anhydrous ethanol and PEG2000 were added to the ball mill in a mass ratio of 25% and 1% to the raw powder, respectively. During the ball milling process, 0.06 MPa argon gas was filled for protection. After the ball milling, a 400-mesh sieve was used for filtration. Spray drying was then performed, and the atomizing disk speed during spray drying was 2.0 6000r / min, drying temperature is 110℃; during the sintering process of the powder agglomerate after spray drying, the initial vacuum degree is 2Pa, the heating rate is 5℃ / min, the temperature is kept at 500℃ for 1h during the sintering process, and the furnace is cooled after the sintering is completed; then crushing and air flow classification are carried out to prepare AlCoCrFeNiCu high entropy alloy powder with an average particle size of 32μm; AlCoCrFeNiCu high entropy alloy powder is used to supersonic flame spray the surface of the substrate to form an amorphous ceramic coating, and the hydrogen flow rate during spraying is 560m 3 / s, oxygen flow rate 180m 3 / s, nitrogen flow rate 18m 3 / s, spray distance 200mm, powder feeding rate 40g / min; the high entropy alloy coating with high-density vacancy defects and lattice distortion defects after spraying, the initial high entropy alloy coating area thickness is 320μm, the coating porosity is 0.6%, the roughness Ra is 5.0μm, the grain size of the coating organization is 1.5μm, the coating phase is FCC+BCC dual-phase structure, the crystalline / amorphous interface formed by the high entropy alloy coating and the amorphous ceramic coating is an irreversible hydrogen trap, and its activation energy is 67kJ / mol;
[0033] (5) Formation of plastic deformation layer on the surface of high entropy alloy coating: The high entropy alloy coating was first micro-sandblasted with 2 μm Al2O3 powder. The sandblasting pressure was 0.08 MPa, the sandblasting angle was 45°, and the sandblasting distance was 50 mm. After sandblasting for 1 min, ultrasonic cleaning was performed in anhydrous ethanol for 15 min. The ultrasonic frequency and power during ultrasonic cleaning were 40 kHz and 100 kHz, respectively. W, ultrasonic cleaning and cold air drying; then the surface of the high entropy alloy coating is roller burnished with a diamond indenter with a tip arc radius of 1.0 mm, the linear speed of the roller burnishing is 70 m / min, the feed rate is 0.05 mm / r, the pre-pressing amount is 0.01 mm, the load is 100 N, and the angle between the axis of the indenter and the normal line of the surface of the high entropy alloy coating is 30 °. During the roller burnishing process, the diamond indenter causes severe plastic deformation on the coating surface, and the high points of the surface contour flow into the low points. After roller burnishing, the surface roughness of the high entropy alloy coating is Ra0.06, and a plastic deformation layer is formed on the surface of the coating. The thickness of the initial plastic deformation layer is 15 μm, the grain size of the plastic deformation layer organization is 43 nm, and the porosity is 0.03%. The phase of the plastic deformation layer remains a FCC+BCC dual-phase structure.
[0034] (6) Oxidation treatment of the surface plastic deformation layer: The substrate formed with the surface plastic deformation layer of the high entropy alloy coating is placed in a vacuum furnace for oxidation treatment in an argon and oxygen mixed atmosphere. The oxygen content in the argon and oxygen mixed atmosphere is 2 vol%. During the oxidation treatment, the vacuum in the furnace is first evacuated to 1.5*10 -2 Pa, the heating rate of oxidation treatment is V=6℃ / min, the oxidation temperature is controlled at 921℃, the oxidation time is 1h, and after the treatment, Ar gas with a flow rate of 50L / h is introduced for rapid cooling. A dense Al2O3 ceramic oxide film with a thickness of 1.3μm is generated in situ on the surface of the plastic deformation layer. The dangling bond density in the SiC-MWCNT-Ni metal ceramic composite layer remains unchanged, the amorphous ceramic coating remains amorphous and no crystalline phase is precipitated, and the phase of the high entropy alloy coating remains unchanged;
[0035] (7) Preparation of low-emission liquid hydrogen valve material with amorphous / crystalline interface: First, the substrate surface after surface plastic deformation layer oxidation treatment was ground with W0.5 and W0.25 grinding pastes in turn, and the surface roughness reached Ra0.08, and then ultrasonic cleaning was carried out in anhydrous ethanol for 10 minutes. The ultrasonic frequency and power during ultrasonic cleaning were 40 kHz and 100 W respectively. After ultrasonic cleaning, it was blown dry with cold air, and then the blown-dried valve stem, valve stem and valve cover substrate were assembled with matching packing, spring and bearing parts. The preparation of low-emission liquid hydrogen valve material with amorphous / crystalline interface was completed. Its minimum service temperature was -269℃, the maximum working pressure was 70MPa, and its permeability reduction factor PRF was 320. The liquid hydrogen valve made of low-emission liquid hydrogen valve material with amorphous / crystalline interface was tested according to ISO 15848-1 and GB / T 40079 standards. The leakage rate of the valve stem seal was ≦2.25*10 -8 mg·s -1 mm -1 , the leakage at the valve body seal is 46ppmv.
[0036] Example 2:
[0037] A low-emission liquid hydrogen valve material with an amorphous / crystal interface, the structure of which is as follows Figure 1 As shown in the figure, the substrate is carbon steel, alloy steel or stainless steel, and the surface of the substrate is composed of a SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds, an Al2O3-ZrO2-YAG amorphous ceramic coating, and a high-entropy alloy coating. The SiC-MWCNT-Ni metal ceramic composite layer is 43 μm thick and contains 3×10 18 / cm 3High-density C- and Si-dangling bonds; the thickness of the Al2O3-ZrO2-YAG amorphous ceramic coating is 180μm, the porosity is 1.3%, and the crystalline / amorphous interface formed by the amorphous ceramic coating and the SiC-MWCNT-Ni metal ceramic composite layer is an irreversible hydrogen trap with an activation energy of 72kJ / mol; the high-entropy alloy coating is AlCoCrFeNiCu, with a molar ratio of Al:Co:Cr:Fe:Ni:Cu= 1.1:1:1.2:1:1:1, and there are high-density vacancy defects and lattice distortion defects in the coating. The initial high-entropy alloy coating area is 340μm thick, the coating porosity is 0.8%, and the roughness Ra 6μm, the grain size of the coating organization is 2.1μm, the coating phase is FCC+BCC dual-phase structure, the crystalline / amorphous interface formed by the high entropy alloy coating and the amorphous ceramic coating is an irreversible hydrogen trap, and its activation energy is 68kJ / mol. The surface of the AlCoCrFeNiCu high entropy alloy coating has a plastic layer formed by rolling. The thickness of the initial plastic layer is 26μm, the grain size of the plastic layer organization is 33nm, the porosity is 0.02%, and the phase of the plastic layer remains FCC+B CC dual-phase structure, the surface of the plastic deformation layer has an in-situ generated 2.1μm thick dense Al2O3 ceramic oxide film, and the surface roughness after grinding is Ra0.09; the minimum service temperature of the low-emission liquid hydrogen valve material with amorphous / crystalline interface of the present invention is -269℃, the maximum working pressure is 70MPa, and its permeability reduction factor PRF is 430; the leakage rate of the valve stem seal of the liquid hydrogen valve made of the low-emission liquid hydrogen valve material with amorphous / crystalline interface is ≦1.94*10 -8 mg·s -1 mm -1 , the leakage at the valve body seal is 41ppmv.
[0038] The preparation method of the material is as follows Figure 2 As shown, the following steps are included:
[0039] (1) Preparation of SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds: Carbon steel, alloy steel or stainless steel is used as the substrate and processed into the valve stem, valve body or valve cover of the liquid hydrogen valve. The substrate surface is firstly subjected to micro-sandblasting treatment with white corundum micropowder with a particle size of 320 mesh to roughen the surface. The sandblasting pressure is 0.1 MPa, the sandblasting angle is 75°, and the sandblasting distance is 65 mm. After sandblasting for 8 minutes, it is ultrasonically cleaned in anhydrous ethanol for 20 minutes. The ultrasonic frequency and power during ultrasonic cleaning are 40 kHz and 100 W, respectively, and cold air drying is used. Then, the substrate with an average particle size of 56 nm and a specific surface area of 87 m 2 / g of nano-SiC powder, with a diameter of 16nm, a length of 12μm, and a specific surface area of 220m 2 / g of multi-walled carbon nanotubes MWCNT, mixed with NiSO4, NiCl2, and H3BO3 to prepare a mixed solution, wherein the NiSO4 concentration is 260g / L, the NiCl2 concentration is 38g / L, the H3BO3 concentration is 36g / L, the nano-SiC content is 2.7g / L, and the multi-walled carbon nanotube MWCNT content is 0.5g / L. The mixed solution is ultrasonically treated for 35min, and the ultrasonic frequency and power during the ultrasonic treatment are 40 kHz and 100 W, respectively. Then, Tween80 is added dropwise according to 2% of the volume of the mixed solution, and HCl is added dropwise to adjust the pH value of the mixed solution to 4. A composite electrodeposition solution with a Zeta potential of 24mv is obtained while the mixture is added dropwise and magnetically stirred. The substrate is placed in the composite electrodeposition solution as a cathode, and a pure Ni plate is used as an anode. The current density is controlled to be 4A / dm 2 , pulse frequency 1000 Hz, pulse duty cycle 40%, electrodeposition temperature 55 ° C, deposition time 60 min, a 43 μm thick layer containing 3×10 18 / cm 3 SiC-MWCNT-Ni metal ceramic composite layer with high density of C- and Si-dangling bonds;
[0040] (2) Preparation of eutectic ceramic feed powder: First, C 16 H 33 (CH3)3NBr, isopropanol, and n-hexane were added to deionized water, and the weight percentage was C 16 H 33 (CH3)3NBr accounts for 22%, isopropanol accounts for 13%, n-hexane accounts for 12%, and the rest is ionized water. Stir with a magnetic stirrer at 80℃ for 7h, and then leave it for 7h to form a reverse microemulsion. Weigh Al(NO3)3, ZrOCl2, and Y(NO3)3. The molar ratio of the three reagents is 0.63:0.27:0.1. Add the three reagents to the prepared reverse microemulsion to control the total molar concentration of the three reagents to 0.7mol / L. Then add ammonia water to adjust the pH value of the solution to 9. Stir with a magnetic stirrer at 90℃ for 8h. Then, the mixture was placed for 20 hours to form an Al(OH)3-Zr(OH)4-Y(OH)3 eutectic precursor sol, 2 wt.% PVA was added, and then spherical powder agglomerates were prepared by spray drying. The spherical powder agglomerates were placed in a vacuum sintering furnace, the initial vacuum degree of sintering was 4 Pa, the heating rate was 8 ° C / min, the temperature was kept at 550 ° C for 1 hour during the sintering process, and the temperature was sintered at 1500 ° C for 90 minutes. After the sintering was completed, the furnace was cooled to obtain a eutectic ceramic feed powder with a particle size of 38 μm and a phase composition of α-Al2O3, c-ZrO2 and YAG phase, i.e., Y3Al5O 12 ;
[0041] (3) Preparation of amorphous ceramic coating: First, the substrate on which the SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds was formed was placed in liquid nitrogen for 2 hours to cool it to -185°C; the substrate surface that had been cooled to below -185°C was plasma sprayed with eutectic ceramic feed powder. The spraying current was 650A, the power was 45kW, the argon flow rate was 45L / min, the hydrogen flow rate was 7L / min, the powder feeding rate was 32g / min, and the spraying distance was 110mm; during the thermal spraying process, the substrate was cooled with 0.8MPa compressed air to form an Al2O3-ZrO2-YAG amorphous ceramic coating with a thickness of 180μm and a porosity of 1.3% under high supercooling. The crystalline / amorphous interface formed by the amorphous ceramic coating and the SiC-MWCNT-Ni metal ceramic composite layer is an irreversible hydrogen trap with an activation energy of 72kJ / mol;
[0042] (4) Preparation of surface high entropy alloy coating: Al, Co, Cr, Fe, Ni, and Cu powders were weighed in a molar ratio of 1.1:1:1.2:1:1:1, and the weighed raw material powders were subjected to planetary ball milling at a ball milling speed of 380 r / min and a ball-to-material ratio of 10:1. Al2O3 ceramic grinding balls with a diameter of 5 mm were used for ball milling for 40 h. Anhydrous ethanol and PEG2000 were added to the ball mill in a mass ratio of 30% and 2% to the raw material powder, respectively. During the ball milling process, 0.08 MPa argon gas was filled for protection. After the ball milling, a 400-mesh screen was used for filtration. Spray drying was then performed, and the atomizing disk speed during spray drying was 2.5 7000r / min, drying temperature is 120℃; during the sintering process of the powder agglomerate after spray drying, the initial vacuum degree is 4Pa, the heating rate is 8℃ / min, the temperature is kept at 550℃ for 1h during the sintering process, and the furnace is cooled after the sintering is completed; then crushing and air flow classification are carried out to prepare AlCoCrFeNiCu high entropy alloy powder with an average particle size of 36μm; AlCoCrFeNiCu high entropy alloy powder is used to perform supersonic flame spraying on the surface of the substrate to form an amorphous ceramic coating, and the hydrogen flow rate during spraying is 580m 3 / s, oxygen flow rate 190m 3 / s, nitrogen flow rate 20m 3 / s, spray distance 240mm, powder feeding rate 45g / min; the high entropy alloy coating with high-density vacancy defects and lattice distortion defects after spraying, the initial high entropy alloy coating area thickness is 340μm, the coating porosity is 0.8%, the roughness Ra is 6.0μm, the grain size of the coating organization is 2.1μm, the coating phase is FCC+BCC dual-phase structure, the crystalline / amorphous interface formed by the high entropy alloy coating and the amorphous ceramic coating is an irreversible hydrogen trap, and its activation energy is 68kJ / mol;
[0043] (5) Formation of plastic deformation layer on the surface of high entropy alloy coating: The high entropy alloy coating was first micro-sandblasted with 5 μm Al2O3 powder. The sandblasting pressure was 0.08 MPa, the sandblasting angle was 50°, and the sandblasting distance was 60 mm. After sandblasting for 2 min, ultrasonic cleaning was performed in anhydrous ethanol for 20 min. The ultrasonic frequency and power during ultrasonic cleaning were 40 kHz and 100 kHz, respectively. W, and then cold air drying was adopted after ultrasonic cleaning; then a diamond indenter with a tip arc radius of 1.0 mm was used to perform roller burnishing on the surface of the high entropy alloy coating, the linear speed of the roller burnishing was 120 m / min, the feed rate was 0.1 mm / r, the pre-pressing amount was 0.02 mm, the load was 160 N, and the angle between the axis of the indenter and the normal line of the surface of the high entropy alloy coating was 50°. During the roller burnishing process, the diamond indenter caused severe plastic deformation on the surface of the coating, and the high points of the surface contour flowed into the low points. After roller burnishing, the surface roughness of the high entropy alloy coating was Ra0.08, and a plastic deformation layer was formed on the surface of the coating. The thickness of the initial plastic deformation layer was 26 μm, the grain size of the plastic deformation layer was 33 nm, and the porosity was 0.02%. The phase of the surface plastic deformation layer remained as a FCC+BCC dual-phase structure.
[0044] (6) Oxidation treatment of the surface plastic deformation layer: The substrate formed with the surface plastic deformation layer of the high entropy alloy coating is placed in a vacuum furnace for oxidation treatment in an argon and oxygen mixed atmosphere. The oxygen content in the argon and oxygen mixed atmosphere is 4 vol%. During the oxidation treatment, the vacuum in the furnace is first evacuated to 1.5*10 -2 Pa, the heating rate of oxidation treatment is V=10℃ / min, the oxidation temperature is controlled at 927℃, the oxidation time is 1.5h, and after the treatment, Ar gas with a flow rate of 56L / h is introduced for rapid cooling. A dense Al2O3 ceramic oxide film with a thickness of 2.1μm is generated in situ on the surface of the plastic deformation layer. The dangling bond density in the SiC-MWCNT-Ni metal ceramic composite layer remains unchanged, the amorphous ceramic coating remains amorphous and no crystalline phase is precipitated, and the phase of the high entropy alloy coating remains unchanged;
[0045] (7) Preparation of low-emission liquid hydrogen valve material with amorphous / crystalline interface: First, the substrate surface after surface plastic deformation layer oxidation treatment was ground with W0.5 and W0.25 grinding pastes in turn, and the surface roughness reached Ra0.09, and then ultrasonic cleaning was carried out in anhydrous ethanol for 15 minutes. The ultrasonic frequency and power during ultrasonic cleaning were 40 kHz and 100 W respectively. After ultrasonic cleaning, it was blown dry with cold air, and then the blown-dried valve stem, valve stem and valve cover substrate were assembled with matching packing, spring and bearing parts. The preparation of low-emission liquid hydrogen valve material with amorphous / crystalline interface was completed. Its minimum service temperature was -269℃, the maximum working pressure was 70MPa, and its permeability reduction factor PRF was 430. The liquid hydrogen valve made of low-emission liquid hydrogen valve material with amorphous / crystalline interface was tested according to ISO 15848-1 and GB / T 40079 standards. The leakage rate of the valve stem seal was ≦1.94*10 -8 mg·s -1 mm -1 , the leakage at the valve body seal is 41ppmv.
Claims
1. A low-emission liquid hydrogen valve material with an amorphous / crystalline interface, characterized in that The substrate is carbon steel, alloy steel or stainless steel. On the surface of the substrate material, there are SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds, Al2O3-ZrO2-YAG amorphous ceramic coating, and high entropy alloy coating. The SiC-MWCNT-Ni metal ceramic composite layer contains 4×10 17 ~6×10 18 / cm 3 High density of C- and Si-dangling bonds; the crystalline / amorphous interface formed by the Al2O3-ZrO2-YAG amorphous ceramic coating and the SiC-MWCNT-Ni metal ceramic composite layer is an irreversible hydrogen trap, and its activation energy is >70kJ / mol; the high entropy alloy coating is AlCoCrFeNiCu, with a molar ratio of Al:Co:Cr:Fe:Ni:Cu= (1~1.2):1:(1~1.2):1:1:1, and there are high-density vacancy defects and lattice distortion defects in the coating. The grain size of the coating organization is 1.5~2.5μm, and the coating phase is a FCC+BCC dual-phase structure. The crystalline / amorphous interface formed by the high entropy alloy coating and the amorphous ceramic coating is an irreversible hydrogen trap, and its activation energy is >65kJ / mol; the surface of the AlCoCrFeNiCu high entropy alloy coating has a plastic deformation layer formed by rolling, and the grain size of the plastic deformation layer is 30 ~50nm, and its physical phase remains in the FCC+BCC dual-phase structure; the surface of the plastic deformation layer has a dense Al2O3 ceramic oxide film of 1~2.5μm thick generated in situ; the minimum service temperature of the low-emission liquid hydrogen valve material with amorphous / crystalline interface is -269℃, the maximum working pressure is 70MPa, and the permeability reduction factor PRF is 300~500; the leakage rate of the valve stem seal of the liquid hydrogen valve made of the low-emission liquid hydrogen valve material with amorphous / crystalline interface is ≤3.14×10 -8 mg·s -1 mm -1 , the leakage at the valve body seal is ≤50ppmv.
2. According to claim 1, the low-emission liquid hydrogen valve material with an amorphous / crystal interface is further characterized in that the thickness of the SiC-MWCNT-Ni metal ceramic composite layer is 30~45μm; the thickness of the Al2O3-ZrO2-YAG amorphous ceramic coating is 100~200μm, and the porosity is 1.0~1.5%; the thickness of the initial high-entropy alloy coating area is 300~350μm, the porosity is 0.5~1.0%, and the roughness is Ra5.0~6.5μm; the thickness of the initial plastic layer area is 10~30μm, and the porosity of the plastic layer organization is 0.01~0.1%; the surface roughness of the Al2O3 ceramic oxide film on the surface of the plastic layer after grinding is Ra0.08~0.
1.
3. A method for preparing a low-emission liquid hydrogen valve material with an amorphous / crystalline interface, characterized in that The following steps are included in sequence: (1) Preparation of SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds: Using carbon steel, alloy steel or stainless steel as the substrate, first use white corundum micropowder with a particle size of 240-320 mesh to micro-sandblast the substrate surface to roughen the surface. The sandblasting pressure is 0.1 MPa, the sandblasting angle is 65-85°, and the sandblasting distance is 50-70 mm. After sandblasting for 5-10 minutes, ultrasonic cleaning is carried out in anhydrous ethanol for 15-30 minutes and cold air drying is used. Then, the average particle size is 50-60 nm and the specific surface area is 80-90 m 2 / g of nano-SiC powder, with a diameter of 10~20nm, a length of 5μm~15μm, and a specific surface area of 200~230m 2 / g of multi-walled carbon nanotubes MWCNT are mixed with NiSO4, NiCl2, and H3BO3 to prepare a mixed solution, wherein the concentration of NiSO4 is 230-280g / L, the concentration of NiCl2 is 30-40g / L, the concentration of H3BO3 is 30-40g / L, the content of nano-SiC is 2.5-3g / L, and the content of multi-walled carbon nanotubes MWCNT is 0.4-0.6g / L. After the mixed solution is ultrasonically treated for 30-40min, Tween 80 is added dropwise according to 1-2% of the volume of the mixed solution, and HCl is added dropwise to adjust the pH value of the mixed solution to 3-4.
5. A composite electrodeposition solution with a Zeta potential of 20-25mv is obtained while adding dropwise and magnetic stirring. The substrate is placed in the composite electrodeposition solution as a cathode, and a pure Ni plate is used as an anode. The current density is controlled to be 2.5-4.5A / dm 2 , pulse frequency 1000Hz, pulse duty cycle 30~50%, electrodeposition temperature 50~60℃, deposition time 40~60min, a layer with a thickness of 30~45μm and containing 4×10 17 ~6×10 18 / cm 3 SiC-MWCNT-Ni metal ceramic composite layer with high density of C- and Si-dangling bonds; (2) Preparation of eutectic ceramic feed powder: First, C 16 H 33 (CH3)3NBr, isopropanol, and n-hexane were added to deionized water, and the weight percentage was C 16 H 33 (CH3)3NBr accounts for 15% to 32%, isopropanol accounts for 7% to 15%, n-hexane accounts for 6% to 15%, and the rest is deionized water. Stir with a magnetic stirrer at 60 to 90 ° C for 3 to 10 hours, and then place it for 6 to 12 hours to form a reverse microemulsion; weigh Al(NO3)3, ZrOCl2, and Y(NO3)3, the molar ratio of the three reagents is 0.63: (0.37-x): x, and x / (0.37-x)=0.04~0.12, add the three reagents to the prepared reverse microemulsion, control the total molar concentration of the three reagents to 0.6~0.8 mol / L, then add ammonia water to adjust the pH value of the solution to 8~9, and stir with a magnetic stirrer at 60 to 90 ° C for 3 to 12 hours. Then, the mixture was placed for 10 to 24 hours to form an Al(OH)3-Zr(OH)4-Y(OH)3 eutectic precursor sol, 1 to 2 wt.% PVA was added, and then spherical powder agglomerates were prepared by spray drying. The spherical powder agglomerates were placed in a vacuum sintering furnace and sintered at 1400 to 1500 °C for 60 to 90 minutes to obtain a eutectic ceramic feed powder with a particle size of 30 to 40 μm and a phase composition of α-Al2O3, c-ZrO2 and YAG phase, i.e., Y3Al5O 12 ; (3) Preparation of amorphous ceramic coating: First, the substrate on which the SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds was formed was placed in liquid nitrogen for 1 to 2 hours to cool it to below -180°C; the substrate surface that had been cooled to below -180°C was plasma sprayed with eutectic ceramic feed powder. The current during spraying was 600 to 650A, the power was 35 to 45kW, the argon flow rate was 45L / min, the hydrogen flow rate was 7L / min, the powder feeding rate was 30 to 35g / min, and the spraying distance was 100 to 120mm; an Al2O3-ZrO2-YAG amorphous ceramic coating with a thickness of 100 to 200μm and a porosity of 1.0 to 1.5% was formed under high supercooling. The crystalline / amorphous interface formed between the amorphous ceramic coating and the SiC-MWCNT-Ni metal ceramic composite layer was an irreversible hydrogen trap with an activation energy of >70kJ / mol; (4) Preparation of surface high entropy alloy coating: Al, Co, Cr, Fe, Ni, and Cu powders were weighed in a molar ratio of (1-1.2):1:(1-1.2):1:1:1, and the weighed raw material powders were subjected to planetary ball milling at a ball milling speed of 300-400 r / min and a ball-to-material ratio of 10:
1. Al2O3 ceramic grinding balls with a diameter of 5 mm were used for ball milling for 24-48 h. After ball milling, AlCoCrFeNiCu high entropy alloy powder with an average particle size of 30-40 μm was prepared by filtration, spray drying, agglomeration sintering, crushing, and air flow classification. The AlCoCrFeNiCu high entropy alloy powder was used to form an amorphous ceramic coating on the substrate surface by supersonic flame spraying. The hydrogen flow rate during spraying was 560-580 m 3 / s, oxygen flow rate 180~200m 3 / s, nitrogen flow rate 18~20m 3 / s, spray distance 200~250mm, powder feeding rate 40~45g / min; The high entropy alloy coating with high-density vacancy defects and lattice distortion defects produced after spraying has an initial high entropy alloy coating area thickness of 300-350μm, a coating porosity of 0.5-1.0%, a roughness Ra of 5.0-6.5μm, a coating grain size of 1.5-2.5μm, a coating phase of FCC+BCC dual-phase structure, and a crystalline / amorphous interface formed by the high entropy alloy coating and the amorphous ceramic coating as an irreversible hydrogen trap with an activation energy of >65kJ / mol. (5) Formation of plastic deformation layer on the surface of high entropy alloy coating: The surface of high entropy alloy coating was rolled using a diamond indenter with a tip arc radius of 1.0 mm. The linear speed of the rolling process was 50-200 m / min, the feed rate was 0.05-0.15 mm / r, the pre-pressing amount was 0.01-0.03 mm, the load was 100-200 N, and the angle between the indenter axis and the surface normal of the high entropy alloy coating was 30-60°. During the rolling process, the diamond indenter caused severe plastic deformation on the coating surface, and the high points of the surface contour flowed into the low points. After rolling, the surface roughness of the high entropy alloy coating was Ra0.06-0.08, and a plastic deformation layer was formed on the surface of the coating. The thickness of the initial plastic deformation layer was 10-30 μm, the grain size of the plastic deformation layer was 30-50 nm, and the porosity was 0.01-0.1%. The phase of the plastic deformation layer remained a FCC+BCC dual-phase structure. (6) Oxidation treatment of the surface plastic deformation layer: The substrate with the surface plastic deformation layer of the high entropy alloy coating is placed in a vacuum furnace for oxidation treatment in a mixed atmosphere of argon and oxygen. The heating rate V = 5~15℃ / min. The relationship between the oxidation temperature and the heating rate is, oxidation temperature = (900+12lnV)℃, and the oxidation time is 1~2h. After the treatment, Ar gas with a flow rate of 50~60L / h is introduced for rapid cooling. A dense Al2O3 ceramic oxide film with a thickness of 1~2.5μm is generated in situ on the surface of the plastic deformation layer. The dangling bond density in the SiC-MWCNT-Ni metal ceramic composite layer remains unchanged. The amorphous ceramic coating remains amorphous and no crystalline phase is precipitated. The physical phase of the high entropy alloy coating remains unchanged. (7) Preparation of low-emission liquid hydrogen valve material with amorphous / crystalline interface: First, the substrate surface after surface plastic deformation layer oxidation treatment was ground with W0.5 and W0.25 grinding pastes in turn, and the surface roughness reached Ra0.08~0.1, then ultrasonically cleaned in anhydrous ethanol for 10~15min and dried with cold air, and then the dried valve stem, valve stem and valve cover substrate were assembled with matching packing, spring and bearing parts, and the preparation of low-emission liquid hydrogen valve material with amorphous / crystalline interface was completed. Its minimum service temperature was -269℃, the maximum working pressure was 70MPa, and its permeability reduction factor PRF was 300~500; the leakage rate of the valve stem seal of the liquid hydrogen valve made of low-emission liquid hydrogen valve material with amorphous / crystalline interface was ≤3.14×10 -8 mg·s -1 mm -1 , the leakage at the valve body seal is ≤50ppmv.
4. The method for preparing a low-emission liquid hydrogen valve material having an amorphous / crystalline interface according to claim 3, further characterized in that: (1) When preparing a SiC-MWCNT-Ni metal ceramic composite layer containing high-density dangling bonds, the base material is first processed into a valve stem, valve body or valve cover of a liquid hydrogen valve; the ultrasonic frequency and power during ultrasonic cleaning and ultrasonic treatment are 40 kHz and 100 W, respectively; (2) When preparing eutectic ceramic feed powder, the initial vacuum degree of sintering is 1~5Pa, the heating rate is 5~10℃ / min, and the sintering process is first kept at 500~550℃ for 1h, and then cooled with the furnace after sintering at 1400~1500℃; (3) When preparing amorphous ceramic coatings, compressed air at 0.6-0.8 MPa is used to cool the substrate during thermal spraying; (4) When preparing AlCoCrFeNiCu high entropy alloy powder, anhydrous ethanol and PEG2000 were added to the ball mill, and the mass ratio of the added amount to the raw material powder was 25-30% and 1-2%, respectively. During the ball milling process, 0.05-0.10 MPa argon gas was filled for protection, and a 400-mesh screen was used for filtration after the ball milling. During the spray drying, the atomizing disk speed was 6000-7000 r / min, and the drying temperature was 110-120 °C. During the sintering process of the powder agglomerate after spray drying, the initial vacuum degree was 1-5 Pa, the heating rate was 5-10 °C / min, and the temperature was kept at 500-550 °C for 1 h during the sintering process. After the sintering was completed, the powder was cooled with the furnace. (5) Before the surface roller treatment of the high-entropy alloy coating, the high-entropy alloy coating was first micro-sandblasted with 2-5 μm Al2O3 micropowder. The sandblasting pressure was 0.08 MPa, the sandblasting angle was 45-55°, and the sandblasting distance was 50-70 mm. After sandblasting for 1-3 min, ultrasonic cleaning was performed in anhydrous ethanol for 15-30 min. The ultrasonic frequency and power during ultrasonic cleaning were 40 kHz and 100 W, respectively. Cold air drying was used after ultrasonic cleaning. (6) During oxidation treatment of the surface plastic deformation layer, the oxygen content in the mixed atmosphere of argon and oxygen is 1~5vol%. During oxidation treatment, the vacuum in the furnace is first drawn to 2×10 -2 Below Pa; (7) When preparing low-emission liquid hydrogen valve materials with amorphous / crystalline interfaces, the ultrasonic frequency and power during ultrasonic cleaning are 40 kHz and 100 W, respectively.
Citation Information
Patent Citations
Chromium plating process used for valve rod
CN102965695A
A hydrogenation valve and its processing method
CN103807458B
Treating method for valve stem of valve
CN107881456A
Toughness, thermal conductive and high-temperature micro-structure stabilization integrated amorphous oxide ceramic composite coating layer preparation method
CN109680241A
Method for depositing high-entropy alloy coating on surface of ceramic-based composite material
CN115537808A